A Decomposed Solution of Multi-energy Flow in Regional Integrated Energy Systems Considering Operational Constraints. (May 2017) - Wang, Weiliang; Wang, Dan; Jia, Hongjie; Chen, Zhaoyu; Tang, Jia
Abstract: With the technology development of energy conversion, multi-energy flow containing electricity, gas and heat is becoming tightly integrated in regional integrated energy systems (RIESs). Interactions and complementarities of various energy systems can bring more environmental and economic benefits but also security problems. This paper studies a decomposed solution of multi-energy flow considering operational constraints, the energy coupling part is analyzed with the concept of energy hub (EH). Multi-energy flow calculation is verified in case study under conditions of different disturbance in EH, showing the necessarily of operational constraint concern. In addition, a multi-energy flow regulation is discussed utilizing gas load-pressure sensitivity analysis.